Dihydroartemisinin Alleviates Imiquimod-Induced Psoriasis-like Skin Lesion in Mice Involving Modulation of IL-23/Th17 Axis - Liu, Jiang-Min; Jin, Quan-Xin; Fujimoto, Manabu; Li, Fang-Fang; Jin, Lin-Bo; Yu, Ran; Yan, Guang-Hai; Zhu, Lian-Hua; Meng, Fan-Ping; Zhang, Qing-Gao; Jin, Gui-Hua (Frontiers in Pharmacology, 2021)
Background: Psoriasis is a Th17 cells-mediated chronic inflammatory skin disease. Recent studies have shown that dihydroartemisinin (DHA) can significantly reduce experimental autoimmune encephalomyelitis and rheumatoid arthritis by regulating Th17 cells. Objective: To verify whether DHA can improve the symptoms of psoriasis, and to further explore the possible mechanism. Methods: The efficiency of DHA was preliminary detected on HaCaT cells in psoriatic condition. Then imiquimod-induced psoriasis-like model in BALB/c mice was established to evaluate the effects of DHA in vivo. Results: Under the stimulation of TNF-α and IFN-γ, DHA inhibited the proliferation of HaCaT cells, and significantly affected the mRNA expression levels of IFN-γ, IL-17A and IL-23. DHA treatment reduced the severity of psoriasis-like skin and resulted in less infiltration of immune cells in skin lesions. DHA restored the expression of IFN-γ, IL-17A and IL-23 in skins, as well as a decrease of cytokines and chemokines in skin supernatant. DHA also altered the cellular composition in the spleen, which is make up of the T cells, dendritic cells and macrophages. DHA recovered Th17-related profile with decreased frequency of IL-17+CD4+T cells from splenocyte of mice. Furthermore, DHA also inhibited the concentration of IL-17 from Th17 cells and expression of Th17 cell-related transcription factors ROR-γt in vitro. In addition, phosphorylation of STAT3 was significantly reduced in DHA treatment mice, suggesting that the IL-23/IL-17 axis plays a pivotal role. Conclusion: DHA inhibits the progression of psoriasis by regulating IL-23/Th17 axis, and is expected to be an effective drug for the treatment of psoriasis.